Overhead Lines - Papailiou, Konstantin O. (CIGRE Green Books, 2017)
This handbook offers all aspects of Overhead Transmission Lines as the backbone of networks of electrical power. The content of the book includes, after a historical flash-back: Planning and management concepts, electrical and mechanical considerations, influences of the weather, and on the environment, detailed design of all line components, construction and maintenance aspects, line optimization, and asset management, as well as a comparison between overhead lines and underground cables. The book was written by more than 50 experts and assembled through the Cigré study committee on Overhead Lines. This guarantees valuable exchange and dissemination of unbiased information for technical but also non-technical audiences. .